Consumer Purchase Intention towards Organic Food Products in Nepal - Jitendra Prasad Upadhyay,; Ballav Niraula, (Pravaha, 2023)
The main objective of the study is to analyze the factors affecting purchase intention towards organic food products in Nepal, beside, this study analyze the extent to which health consciousness, organic food knowledge, product availability, and price impact the purchase intention of organic foods. Due to the specific nature of research objectives, descriptive-cum- explanatory research design has been used. The target populations of this study constitute people who live in Nepal out of which 384 people have been selected as sample using convenience sampling technique out of which 384 people (200 female and 184 male) have been selected as sample using convenience sampling technique. Both the primary and secondary data has been used in this study. “Five-point Likert scale” has been used for analysis of data. The findings of the study clearly indicate there is significant relationship between Purchase Intension with Health Conscious, Organic Food Knowledge, Product Availability and Price.